Pembuatan Sistem Pakar Penyakit Akibat Merokok Disertai Video Streaming - Arif, Arif; , Umi Fadhilah, S.T, M.Eng; , Mochammad Muslich, S.T, M.Eng (2016)
Cigarette's smoke has been known to induce various diseases. Generally, there is no body organ unaffected by smoke of cigarette. Thereby, almost all parts of body may be damaged by smoking, because one cigarette contains about 4000 chemical compounds with 40 of them can be categorized as toxins or carcinogenic (cause cancer) that are dangerous for our body. The research used method of direct interview with people around author and health experts in order to obtain complete and accurate data. The expert system for diagnosing diseases caused by smoking is equipped with video streaming was developed by using Xampp 1.7.4 software (apache 2.2 web server, PHP, and MySQL), with web designer of Macromedia Dreamweaver 8. Results of the research indicated that the expert system of diseases caused by smoking equipped with video streaming made easier for process of identifying diseases caused by smoking, and from the researches, the disease caused by smoking, can be known. A user is only required to select symptoms, and he or she will see results of data questions from previous page. Based on results of system analysis and after designing the system, information of diseases, hospitals, and references can be generated. The expert system of diseases caused by smoking with video streaming can facilitate process of identifying diseases caused by smoking.